ANALISIS KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN PINRANG - Muhammad Alif Khadafi (Journal AK-99, 2022)
This research was conducted at the Regional Finance Agency of Pinrang Regency with interview, observation and documentation data collection techniques, as well as using qualitative descriptive methods. This study aims to determine the application of Government Accounting Standards affect the quality of financial reports in the Pinrang Regency Government. The results of the research on the financial statements of the local government of Pinrang Regency meet the requirements to be said to be of high quality because it has fulfilled 3 main requirements, namely properly accounted for, fully reported by fulfilling the requirements 1) Relevant 2) Reliable 3) Comparable and 4) understandable, and independently audited. The application of accrual-based accounting standards is still being applied slowly because it requires strong resources to implement it gradually.